Karakterisasi Fisik dan Mutu (Kadar Air, Asam Lemak Bebas, dan Angka Lempeng Total) Virgin Coconut Oil (VCO) yang Diperkaya dengan Fermentasi Ragi Roti - Bigi Undadraja; Widia Rini Hartari (Universitas Islam Raden Rahmat, Malang, 2024)
The Virgin Coconut Oil (VCO) fermentation method with baker's yeast is a method that can maintain the quality of the oil. The aim of this research is to determine the quality characteristics of VCO. The research was carried out with three repetitions, and the data obtained was discussed descriptively. The research results showed that the VCO produced by adding 1 gram, 2 gram, and 3 gram of bread yeast still met quality standards in terms of physical characteristics and peroxide value in accordance with SNI 7381:2008, namely a maximum of 2 meq/kg. The parameters of water content and free fatty acid content are in accordance with quality standards according to the APCC (Asian Pacific Coconut Community). And analysis of the total plate number obtained is still within the standard for drinkability, namely 1.0 x 101 CFU/ml.